Unequal Impact of Price Changes in Indonesia - Pratikno, Ruly; Ikhsan, Mohamad (UI Scholars Hub, 2015)
The main idea of this study is to determine the impact of relative inflation on poverty incidents and to investigate whether inflation inequality has occurred in Indonesia. Interesting results were found at regional level. Firstly, Jakarta had different poverty response with respect to price increases. Processed food and transportation inflation were more imperative for the poor in Jakarta. Secondly, the poor in province with low poverty figures were more prone to inflation. In general, the results show that food inflation has the major adverse impact on the poor. Moreover, we found that inflation in Indonesia has not been pro-poor.